POSITION OF LOGISTIC SERVICE PROVIDER IN VEHICLE LOGISTICS - Cempírek, Václav; Kampf, Rudolf (Doprava a spoje, 2005)
There is new supplier field of action in new supplier-customer relations, that but assumes adequate know-how and innovational potentional. Nevertheless only supply of produced components system is not sufficiently presumption for assuring of future profit. It should be accepted by suppliers not only in car industry. They bear the responsibility for innovational products, quality ensuring and increase of customer benefit value so called competitive advantage. Passenger cars producers are still looking for ways leading to reduction of own production depth and subsequently expand and internationalize customer markets (global sourcing). According to optimistic estimations it can be achieved up to 36%.